2020
DOI: 10.1016/j.biopha.2020.110738
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas13: A potential therapeutic option of COVID-19

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 78 publications
(92 reference statements)
0
52
0
Order By: Relevance
“…This is a limitation for any antigen and antibody-based rapid detection kit ( Hou et al, 2020 ). Recently, a CRISPR based fast and highly accurate diagnostic approach for COVID-19 has been introduced which employs nucleic acid readout of SARS-COV-2 ( Lotfi and Rezaei, 2020 ). However, its implementation is highly challenging.…”
Section: Diagnostic Methods Therapeutic Strategies and Government Inmentioning
confidence: 99%
“…This is a limitation for any antigen and antibody-based rapid detection kit ( Hou et al, 2020 ). Recently, a CRISPR based fast and highly accurate diagnostic approach for COVID-19 has been introduced which employs nucleic acid readout of SARS-COV-2 ( Lotfi and Rezaei, 2020 ). However, its implementation is highly challenging.…”
Section: Diagnostic Methods Therapeutic Strategies and Government Inmentioning
confidence: 99%
“…CRISPR/Cas has been developed as a powerful and promising tool for gene therapy ( Lotfi and Rezaei, 2020 ; Zeballos and Gaj, 2020 ; Ferrari et al, 2021 ; Zhang, 2021 ). There are many CRISPR/Cas studies on preclinical and clinical treatments of various diseases, including cancers and infectious diseases.…”
Section: Wide Use Of Crispr/cas In Clinical and Preclinical Researcmentioning
confidence: 99%
“…In another study, Nguyen et al (2020) reported that near-about 10,333 guide RNAs have been specifically designed to target ten peptide-coding regions of the SARS-CoV-2 RNA genome. Interestingly, a diagnostic technique based on CRISPR technology called Specific High-sensitivity Enzymatic Reporter unlocking (SHERLOCK), also known as SHERLOCKv2 was reported, which uses multiple Cas13 enzymes and other enzymes, like Csm6, which exhibits RNase activity when activated by some of the Cas13 nuclease products ( Lotfi and Rezaei, 2020 ). The First CRISPR-based detection kit was approved by the FDA that can diagnose the SARS-CoV-2 infection within an hour.…”
Section: Hla Genetics and Covid-19mentioning
confidence: 99%